Simultaneous effects of irrelevant speech, temperature and ventilation rate on performance and satisfaction in open-plan offices. (December 2015) - Varjo, Johanna; Hongisto, Valtteri; Haapakangas, Annu; Maula, Henna; Koskela, Hannu; Hyönä, Jukka
Abstract: The aim of this study was to investigate how irrelevant speech, temperature and ventilation rate together affect cognitive performance and environmental satisfaction in open-plan offices. In Condition A, neutral temperature (23.5 °C), low intelligibility of speech (high absorption and low masking sound level) and high fresh air supply rate (30 l/s per person) were applied. This was contrasted to Condition B with high room temperature (29.5 °C), highly intelligible speech (low absorption and high masking sound level) and a negligible fresh air supply rate (2 l/s per person). Sixty-five participants were tested. In Condition B, performance decrement was observed especially in working memory tasks. Based on subjective assessments, mental workload, cognitive fatigue and symptoms were higher and environmental satisfaction was lower in Condition B. It was concluded that special attention should be paid to the design of whole indoor environment in open-plan offices to increase subjective comfort and improve performance. Highlights: A large experimental study was performed in an open-plan office environment. Room acoustic design, ventilation rate and room temperature were studied. The quality of indoor environment had a significant effect on cognitive performance. Indoor environment should be well designed to improve environmental satisfaction.